Pengaruh Fasilitas, Lokasi, Dan Promosi Terhadap Minat Berkunjung Wisatawan Di Pantai Tanjung Belandang Kabupaten Ketapang, Provinsi Kalimantan Barat - Restiana ana; Umi Farida; Fery Setiawan (UNIVED Press, 2023)
This investigation focuses on analyse the impact of facilities, location and promotion of the significance of visiting tourists at Tanjung Belandang Beach in Ketapang Regency, West Kalimantan Province. The research employed a quantitative methodology. The written response to the research’s question were used to collect data, which was then evaluated utilizing SPSS 18 software program. This research’s population were tourists at Tanjung Belandang Beach in Ketapang Regency, West Kalimantan Province. Samples in this research amounted to 100 using incidental techniques. The results in this study Persially prove that facilities, location and promotion have a significant influence on the interest in visiting. Whereas simultaneously facilities, location and promotion affect the interest in visiting